EFFECTS OF URBANIZATION AND THE GROWTH OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) AS SUPPORTS FOR THE ECONOMY OF INDONESIA IN AN URBAN CONTEXT - Rizki Marman Saputra; Harry Darmawan (Journal of Social Political Sciences, 2023)
Urbanization's impacts on megacities like Jakarta are highlighted, including positive and negative economic and societal effects. The positive influence of urbanization on economic growth is contrasted with negative consequences such as slum areas, pollution, and congestion. The significance of understanding Micro, Small, and Medium Enterprises (MSMEs) and large corporations' roles in economic growth is stressed. MSMEs' importance in microeconomic growth and the significant role of large corporations in macroeconomic expansion are outlined. The study's objective is stated in the Aim, which aims to analyze urban economic data and theories using a descriptive analysis method to provide deeper insights into factors influencing urban economic growth and highlight collaboration between MSMEs and large corporations for sustainable development. In the Conclusion, the study's findings emphasize the complex interaction between urbanization, economic actors, and growth patterns, underscoring the need for a balanced approach to achieve holistic urban development in the face of urbanization and economic dynamics.